Perancangan Video Interaktif Profil Tim Arema Cronus 2016 - Nicholaus Wayong Kabelen; Ramadhani Pratama Putra; Faldi Hendrawan; Widya Adhariyanty Rahayu (Jurnal Desain Komunikasi Visual Asia, 2018)
Football is a sport that is very popular throughout the world, including in Indonesia. Arema Cronus is one of the Indonesian football team which is professionally managed and has big amount of fans. The lack of in-depth information about the profile of the team, coaches and players of Arema Cronus make the fans get a little trouble in finding such information. Designing interactive video is selected to facilitate the search for profile information of Arema Cronus team as well as the latest breakthrough in the delivery of information in the form of interactive video through a web portal Youtube. To support the completion of the study used several methodologies namely literature review conducted by reading a book to learn the theory of shooting to the editing process. Interviews methodology with sources to get the correct information. Observations by direct observation when Arema Cronus held a practice or game. Methods of documentation is used to collect data such as photos or videos. Several stages of the production process those are the object taking photos or video, editing photos, creating layouts with CorelDraw, using Adobe Premiere video editing and uploading videos to Youtube portal. The conclusion of this discussion was to design interactive video as a introduction media of the Arema Cronus profile displayed interface to make it easy to understand, accessible everywhere and everytime. For the future, the design is suggested to have interactive video in the offline version.